1999
DOI: 10.1161/01.str.30.12.2692
|View full text |Cite
|
Sign up to set email alerts
|

Reference Values for Vertebral Artery Flow Volume by Duplex Sonography in Young and Elderly Adults

Abstract: Background and Purpose-Vertebrobasilar ischemia has been attributed to a reduction of net vertebral artery flow volume, the product of mean flow velocity and the cross-sectional area of the vessel. It can be determined by duplex sonography. There are no reference values for vertebral artery flow volume in an age group representative of patients with cerebrovascular disease. Methods-We examined 50 nonvascular neurological patients (age 55.8Ϯ14.0 years). Flow velocities and vessel diameters were recorded in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
78
5
6

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(100 citation statements)
references
References 23 publications
10
78
5
6
Order By: Relevance
“…Our results for CBF volume were also in substantial agreement with those published previously for young women with CBF volume of 730±87 mL/min (20). Most publications dealing with CBF measurements in healthy adults report a decline in CBF with increasing age, mainly due to a reduction of cortical blood flow while only few authors found that global CBF remains constant during healthy normal aging (20,21) It has been also reported that while ICA flow decreases with age, VA flow shows no change (21,22). In the present study, there was no statistically significant correlation between VA, ICA and CBF volumes with age in both groups.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results for CBF volume were also in substantial agreement with those published previously for young women with CBF volume of 730±87 mL/min (20). Most publications dealing with CBF measurements in healthy adults report a decline in CBF with increasing age, mainly due to a reduction of cortical blood flow while only few authors found that global CBF remains constant during healthy normal aging (20,21) It has been also reported that while ICA flow decreases with age, VA flow shows no change (21,22). In the present study, there was no statistically significant correlation between VA, ICA and CBF volumes with age in both groups.…”
Section: Discussionsupporting
confidence: 91%
“…All examinations took place in a dimly lighted room with a comfortable temperature (22)(23)(24) 0 C) after an adaptation period for at least 15 minutes rest in supine position. The ICA and vertebral arteries (VA) of both sides were explored with a 7.5-Mhz linear array transducer of a Toshiba Nemio 20 system.…”
Section: Methodsmentioning
confidence: 99%
“…Įvairių autorių SA hipoplazijos apibrėžimai skiriasi, t. y. skiriasi spindis, už kurį siauresnė SA vadinama hipoplastiška. Autoriai [2,3,4,5] SA vadina hipoplastiška, jei jos spindis mažesnis negu 2 mm, kiti autoriai [6,7], jei jos spindis mažesnis negu 2,5 mm, o autoriai [8,9], jei jos spindis mažesnis nei 3 mm. Duomenys apie SA hipoplazijos paplitimą populiacijoje svyruoja nuo 2-3 proc.…”
Section: įVadasunclassified
“…Vien SA spindžio išmatavimas gali būti nepakankamas veiksnys vertinant SA hipoplazijos reikšmę kraujotakai, todėl dažnai matuojamas ir pratekančio kraujo tūris, kuris nurodo, kaip sumažėja kraujotaka per SA. Pagal apibrėžimą pratekančio kraujo tūris per SA laikomas sumažėjusiu, jei jis per atitinkamą SA mažesnis negu 40 ml/min, o bendras pratekančio kraujo tūris per abi SA yra mažesnis negu 100 ml/min (matuojama ultragarsinio tyrimo metu) [9].…”
Section: įVadasunclassified
“…The VAs are commonly asymmetric in diameter, with the left most often having a larger diameter than the right [13,15]. Beyond this, the VA is subject to little anatomical variation (estimated to be ~5% of subjects).…”
Section: Introductionmentioning
confidence: 99%